Analysis of Seaplane Accident Risk Factors Based on Media/Environment in Teluk Pangpang Water Aerodrome - Prayitno, Hadi; Kumara Haryanto, Gading Tirta Gema; Supardam , Dhian; Cahyo, Dimas Hari (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
In Banyuwangi, seaplane flight operations are conducted by the Banyuwangi Indonesian Aviation Academy with a water aerodrome located in the waters of Teluk Pangpang, Banyuwangi. The purpose of this research is to identify environmental factors that can cause accidents during seaplane flight training at the Teluk Pangpang Water Aerodrome in Banyuwangi. The techniques used in the data collection process include field observations, interviews, and documentation. The sample used in this study was taken from the entire population, which includes all team members involved in the seaplane flight operations at the Banyuwangi Indonesian Aviation Academy. Based on the data collected, it can be concluded that the factors contributing to seaplane accidents include the 4Ms: Man (human factors), Machine (machine factors), Media (media or environmental factors), and Management (management factors). The study found that environmental factors posing risks to seaplane flight activities include high sea waves and bird migration in Teluk Pangpang.